DATA DEPENDENT SYSTEMS AS A TOOL FOR MODELLING OF STOCHASTIC PROCESSES IN TRANSPORT AREA (Perner's Contacts, 2013)
The aim of the paper is short description of possibilities of data dependent systems (DDS) mathematical apparatus using. Basic form of DDS expression is form a stochastic time series of process which can be used to description and modelling of stochastic process, e.g. operational process. The paper contains a briefly characteristics of fundamental terms and equations of time series theory mathematical apparatus, algorithm of a statistically adequate discrete model of stochastically dynamic system and developed strategy application on real process.
Keywords: data dependent system; stochastic operational process; time serie